Helicobacter pylori Treatment: An Overview in 2015 - T.B. Abadi, Amin (Anti-Infective Agents, 2015)
Introduction: H. pylori is a flagellate Gram-negative bacterium living on the mucosal surface of the gastric epithelium. It is accepted that the antibiotic resistance is a major problem for treatment of diseases caused by infectious bacteria. Infection is generally acquired during childhood and persists life-long in the absence of antibiotic treatment. Because of development of quinolone-resistant pathogens, quinolone-based triple therapy is not recommended as first-line therapy. In the case of H. pylori treatment we should also be well prepared to face with H. pylori treatment failures. Methods: To determine current status of the treatment failure, we have investigated recent papers in databases. Results: After the failure of first and second lines therapy of H. pylori infection, a culture-guided therapy has been recommended. Local surveillance of antibiotic resistance for all antibiotics used in H. pylori eradication regimens seems a practically possible suggestion to battle against this mysterious infection. More research is required to develop more effective therapeutic approaches. Conclusion: The main aims should be the maintenance of a high eradication rate of H. pylori and also successful prevention actions of increased antibiotic resistance. The purpose of this review is to provide an overview about the current knowledge of H. pylori treatment in 2015; also suggesting possible solutions for difficulties in close future.
Keywords: Helicobacter pylori